Re-scaling Governance in Berlin’s Creative Economy - Bastian Lange (Culture Unbound: Journal of Current Cultural Research, 2011)
The paper aims at discussing the issue of governance in respect to creative scenes, a central structural element of the creative economy, exemplifying the case of Berlin. Berlin has a fast growing creative industry that has become the object of the city’s development policies and place marketing. The core question is: What are the spatial-organizational driving forces of creativity in Berlin - can they be steered by public administration? I am using Berlin as a reference case to articulate the gap between ’stateled planning’ on the one hand and the organisational practices of self-governed creative scenes on the other. I attempt to demonstrate why a perspective change in terms of re-scaling is necessary, in order to respond to the particular practices of emerging industries and their societal form ’scenes’. By re-scaling I mean the conceptualization of governance in different nonhierarchical organisational as well as spatial scales, based on the observation that scenes are considered to be a central element of the functionality of creative industries.